2015
DOI: 10.1021/jf502500t
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Ameliorated Photodamage by Suppressing the Mitogen-Activated Protein Kinase/Matrix Metalloproteinase Pathway and Nuclear Factor-κB Pathways

Abstract: Ultraviolet (UV) irradiation is one of the most important extrinsic factors contributing to skin photodamage. After UV irradiation, a series of signal transductions in the skin will be activated, leading to inflammatory response and photoaged skin. In this study, fisetin, a flavonol that exists in fruits and vegetables, was investigated for its photoprotective effects. The results revealed that 5-25 μM fisetin inhibits cyclooxygenase-2 (COX-2) and matrix metalloproteinase (MMP)-1, MMP-3, MMP-9 expression induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…Hs68 cells were cultured and exposed to UV irradiation as previously described [53]. Cells were incubated in DMEM without serum in the presence of CAE for 24 h after UVB irradiation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hs68 cells were cultured and exposed to UV irradiation as previously described [53]. Cells were incubated in DMEM without serum in the presence of CAE for 24 h after UVB irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were collected and homogenized with lysis buffer as described in previous studies [53,54]. Equal protein amounts (30 μg) were loaded and separated on sodium dodecyl sulfate polyacrylamide gels and then transferred to a PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that fisetin regulates the phosphoinositide 3-kinase (PI3K)/Akt and Erk signaling pathways (1416). It has also been demonstrated that astrocyte migration is modulated by Rho GTPase/p21-activated kinase (PAK)/Erk-dependent signaling (17).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that the Erk1/2 signaling pathway modulated the cytoskeleton dynamics of astrocytes in a scratch-wound model (17). Fisetin has been shown to play an important role in regulating the PI3K/Akt and Erk pathways (14,16,36). In the present study, fisetin downregulated the Akt and Erk phosphorylation levels in astrocytes in a dose-dependent manner, but had no effect on p38 expression and phosphorylation.…”
Section: Discussionmentioning
confidence: 99%